IMPORTANCE OF LOCAL SALES OF AGRICULTURAL PRODUCTION THROUGH THE CREATION OF SPECIALIZED GASTRO TOURISM PRODUCTS - Шимичевић, Дарио; Снежана, Штетић (Economics of Agriculture, 2011)
Rural tourism is being developed within the specifc attributes which allow different forms of tourism activities. These specifc attributes are preserved environment, rich flora and fauna, local community and its culture, heritage and gastronomy. In other words, the diverse natural and socio-cultural environment provides tourists a unique experience through the diversifcation of tourism products in the rural areas. Unlike the usual tourist movements when food and drink seen as an integral but minor part of an integrated tourist product, and as a necessity without which the individual cannot survive, and are treated as a default part of the tourist travel, and not as important as a complementary or main motive of tourist movements. Such an approach to gastronomy is already obsolete, so in terms of tourism, but also in terms of tourism demand. Options valuation gastronomy certain areas are still numerous and range from gourmet restaurants to traditional tours. All forms of presentation include a specifc area of gastronomy in culinary tourism. The paper will highlight the importance of marketing local agriculture through the creation of specialized gastro tourism products. The paper will also address development opportunities in the gastronomy tour of the Danube region.